Spasmodic Dysphonia: Description of the Disease and Associated Neurologic Disorders - Coelho, Marina Serrato; Macedo, Evaldo; de Oliveira, Marcela Schmidt Braz; Lobo, Paulo; Soccol, Andréa Thomaz; Koerner, Heloisa Nardi (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: Spasmodic dysphonia (SD) is a problem that affects speech and vocalization, one of the most devastating disorders of oral communication. It is characterized by vocal quality tensaestrangulada, harshly and / or interspersed with abrupt vocal attack and a great tension in the vocal tract. The etiology of spasmodic dysphonia is unclear. Some authors point to psychogenic causes, neurological or even unknown.Objective: To assess the prevalence of muscular dystonias and other neurological symptoms in patients with ED.Method: A retrospective study of 10 cases with diagnosis of ED for symptoms and neurological disorders associated.Results: There was a significant predominance of the disease in females (9:1). The average age of onset of symptoms was 32 years, ranging between 14 and 60 years. The mean disease duration was 10 years. Among the patients, 87.5% had a diagnosis of disorders of movement made by a neurologist, including orofacial dystonias (50%), essential tremor (50%) and spastic paraparesis (12%).Conclusion: The presence of movement disorders followed almost all cases of spasmodic dysphonia. More studies are needed to clarify the pathophysiological basis of disease.
Keywords: neuromuscular diseases; voice disorders; dysphonia